Pemanfatan Konservasi Mangrove Pesisir Tangkolak Untuk Mengatasi Rob Laut Bersama Unsika Peduli Mangrove (Studi Kasus Unsika Peduli Mangrove Tangkolak Tahun 2022) - Abadi, Slamet (Jurnal Budiman: Pembangunan dan Pengabdian Masyarakat Nusantara, 2023)
The Unsika Peduli Mangrove activity is a continuous and sustainable mangrove community assistance activity. The concept of this activity wants the mangroves on the Karawang coast to be well maintained in general and especially in Tangkolak as a center for mangrove conservation. Procurement of rare mangroves needs to be done specifically for nurseries, especially the male Avicennia and Avicennia besides the Rhizophora and female Avicennia which have a very large population. Supporters of this activity are assisted by the Kreasi Alam Bahari Tangkolak mangrove community. Mangrove planting method is carried out by involving donors, students and the community around Tangkolak. The planting model still uses the traditional direct planting model without using any tools. Activities carried out in 2022 include 1). Nature Campaign Program, UPM. 2). Unsika Peduli Mangrove and Klambi Loyal Coustumer, 3). World Mangrove Day with Unsika Peduli Mangrove and BEM Unsika Engineering, 4). Unsika Peduli Mangrove and Michelin Jakarta, 5). Unsika Cares for Mangrove and Student Executive Board (BEM) Singaperbangsa University Karawang. Community service activities include planting 4,136 mangrove trees. The assessment of community service activities for the mangrove community is 4,418 (88.37%), meaning that the activity is still in great demand by actors who love the environment, especially mangroves. The Tangkolak mangrove conservation program will develop a cropping pattern with a clump pattern spaced 2 m x 5 m. This pattern will be able to reduce the mortality of the growth of the Tangkolak mangrove seedlings.